A Study to Evaluate the Impact of Health Education on Awareness of Long-term Complications of Hypertension Among Hypertensive Patients in A Selected Hospital, Bengaluru - Madhushree A.V. (International Journal of Evidence Based Nursing And Practices, 2024)
The rising burden of non-communicable diseases, particularly hypertension, poses significant public health challenges, especially in developing nations. This study aimed to assess the effectiveness of a health education program focused on lifestyle modifications to prevent hypertension-related complications among patients at selected hospitals in Bengaluru. Employing a quasi-experimental design, we recruited 60 hypertensive patients through purposive sampling. Initial knowledge was evaluated using a structured questionnaire, followed by an educational intervention provided on the same day. A post-test was conducted eight days later using the same instrument. Results indicated a mean pre-test knowledge score of 13.0%, which increased to 42.65% post-intervention, reflecting a 29.65% gain and a 69.5% overall improvement in knowledge. Statistical analysis, including a paired t-test, demonstrated a t-value of 37.71 and a p-value less than 0.01, confirming the effectiveness of the health education program in enhancing knowledge about hypertension and its long-term complications. These findings reveal a significant knowledge gap among hypertensive patients prior to the intervention, highlighting the necessity for targeted educational efforts. The health education materials, developed by the WHO, effectively communicated critical information, leading to improved patient understanding and engagement in self-management strategies. In conclusion, the study emphasizes the importance of structured health education in empowering hypertensive patients to manage their condition more effectively, thereby reducing the risk of long-term complications associated with hypertension. This approach is essential in addressing the growing prevalence of non-communicable diseases in developing contexts.
Keywords: hypertension; hypertensive patients; placard, knowledge, long-term complications